The impact of pavement materials on surface temperature - Md Mahani, Siti Halijah; Ab Sani, Jasasikin (2016)
Urban heat island refers to the higher of urban area compared to the surrounding rural areas. Previous studies on urban heat island (UHI) often prove the existence of significant effect of land cover on urban surface temperature. The urban heat island (UHI) phenomenon rises as urbanization increases. A key characteristic of urban areas is artificial surfaces, which can absorb and store great amounts of heat throughout the day. While standard pavements like asphalt and concrete have been extensively studied, newly introduced pervious pavements have not been intensively analyzed. My study examined the pavement material of impervious and pervious pavement materials and their association with surface temperatures. As a case study, I investigated an area on the International Islamic University Malaysia, Gombak campus exhibiting open areas of asphalt, brick pavers and pebble wash. I collected the data of material temperatures during the warmest time of day, between 2 p.m. to 4 p.m., using an infrared thermometer for surface temperatures. Using Microsoft excel, I found differences in surface temperatures of each material.